P08.05.B Communication in the context of glioblastoma treatment: what matters most to patients and caregivers. (5th September 2022) - Boele, F W; Butler, S; Nicklin, E; Pointon, L; Short, S C; Murray, L
Abstract: Background: Given the poor prognosis of glioblastoma, with short survival times regardless of treatment, it is critical that the benefits and risks of treatments are clearly discussed with patients and family caregivers. The respective value of quantity versus quality of life varies for each individual. Yet, effective communication can be complicated by emotional responses following diagnosis, patients' neurocognitive deficits, and sometimes, lower health literacy. We aimed to investigate patient and caregiver experiences and preferences around glioblastoma treatment communication. Material and Methods: Semi-structured qualitative interviews were conducted with adult glioblastoma patients and their caregivers, interviewed as dyads or individuals. Purposive sampling was used to capture views across the entire disease trajectory. Interviews were recorded, transcribed verbatim, and analysed for common themes. Analysis is ongoing and will be completed by June 2022, with preliminary findings described below. Results: In total, 15 glioblastoma patients and 13 caregivers took part, 8 as dyads. Five main themes were found. 1) Communication experiences . A rush to get treatment underway can limit adequate communication. Patients and caregivers described that risks of treatment were clearly explained, but perceived it as 'the only option'. 2) Communication preferences . Balanced and sensitive communication of prognostic information was desired, with uncertainty providing hope as well as being a burden. Patients and caregivers can have different information and support needs, requiring separate and proactive communication. 3) What matters most . Participants valued feeling involved, having clear and reliable information and support from the treatment team, and developing a personable relationship. In terms of treatment goals, they valued extending life with good quality of life. 4) Decision-making . Participants emphasised the importance of being involved in decisions, involving caregivers, and following treatment team advice. While faced with extremely limited treatment options, they valued having a sense of control over declining, pausing or stopping treatment. 5) Impact of Covid-19 . In general, patients described limited impact of the measures taken during the pandemic (e.g., masks, telephone consultations), whilst caregivers highlighted specific issues around not being able to support patients in emergencies, expressing/reading nonverbal cues, or fully participating in telephone consultations. Conclusion: Glioblastoma patients and caregivers value sensitive, comprehensive and comprehensible communication around treatment risks and benefits, and supportive care. Involving and supporting caregivers is critical.